2021
DOI: 10.1021/acssuschemeng.1c04798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elemental Sulfur on the Aging Trajectory and Adhesion Characteristics of Rubber-Modified Bitumen

Abstract: This study examines the role of sulfur in rubber-modified bitumen and its response to ultraviolet (UV) exposure in terms of its viscoelasticity, creep recovery, healing behavior, surface chemical oxidation, and surface adhesion. Infrared spectroscopy showed a pronounced enrichment of oxidized sulfur and carbon compounds at the surface of sulfur-modified bitumen after mild heating and especially after UV irradiation. 3% added sulfur increased bitumen plasticity by all measures. UV aging marginally decreased bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Carbonyl growth is an evaluation indicator of the oxidative aging of rubber asphalt. 15 However, it was found that sulfur can retard the growth of carbonyl groups of rubber asphalt in another study. 19 Dynamic vulcanization refers to the behavior of vulcanization during dynamic mixing, which has been widely applied in the preparation of thermoplastic elastomers based on rubber/plastic blends.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Carbonyl growth is an evaluation indicator of the oxidative aging of rubber asphalt. 15 However, it was found that sulfur can retard the growth of carbonyl groups of rubber asphalt in another study. 19 Dynamic vulcanization refers to the behavior of vulcanization during dynamic mixing, which has been widely applied in the preparation of thermoplastic elastomers based on rubber/plastic blends.…”
Section: Introductionmentioning
confidence: 93%
“…Sulfur has almost no effect on carbonyl growth, while it can improve the resistance to hardening and degradation of rubber asphalt. Carbonyl growth is an evaluation indicator of the oxidative aging of rubber asphalt 15 . However, it was found that sulfur can retard the growth of carbonyl groups of rubber asphalt in another study 19 …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Secondly, the release of carbon black from the cross-linked network can bind with asphaltene, preventing the oxidation of asphalt from UV light and oxygen [ 56 ]. In addition, the cross-linking reaction that happened to carbon–carbon double bonds and sulfur-containing bonds brought about a self-healing effect to DRMA, increased fatigue and low-temperature crack resistance [ 58 ].…”
Section: Sustainability Of Rubberized Asphaltmentioning
confidence: 99%